2017
DOI: 10.1088/1361-6463/aa9316
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature sputter-deposited ZnO films with enhanced Hall mobility using excimer laser post-processing

Abstract: We report the low temperature (T<70 ºC) fabrication of ZnO thin films (~140 nm) with Hall mobility of up to 17.3 cm 2 V-1 s-1 making them suitable for thin film transistor (TFT) applications. The films were deposited by rf magnetron sputtering at T<70 ºC and subsequently laser processed in ambient temperature in order to modify the Hall mobility and carrier concentration. Medium-to-low energy laser radiation densities and a high number of pulses were used to avoid damaging the films. Laser annealing of the fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…This device performance is unprecedented for a semiconductor directly grown on a complementary metal oxide semiconductor (CMOS) compatible amorphous oxide at vertical integration/plastic compatible low temperatures. This Te device performance is significantly higher than other low‐temperature grown materials such as poly‐Si and ZnO, which usually exhibit mobilities below 100 cm 2 V −1 s −1 . This performance is also much higher than other synthetic vdW materials like MoS 2 on SiO 2 /Si with a mobility of ≈192 cm 2 V −1 s −1 and comparable to most of the reports of black phosphorus on SiO 2 /Si with mobilities around ≈400 cm 2 V −1 s −1 , with Te having the significant advantage of utilizing a low‐temperature, scalable growth technique, compatible with heterogeneous 3D integration and flexible devices.…”
mentioning
confidence: 92%
“…This device performance is unprecedented for a semiconductor directly grown on a complementary metal oxide semiconductor (CMOS) compatible amorphous oxide at vertical integration/plastic compatible low temperatures. This Te device performance is significantly higher than other low‐temperature grown materials such as poly‐Si and ZnO, which usually exhibit mobilities below 100 cm 2 V −1 s −1 . This performance is also much higher than other synthetic vdW materials like MoS 2 on SiO 2 /Si with a mobility of ≈192 cm 2 V −1 s −1 and comparable to most of the reports of black phosphorus on SiO 2 /Si with mobilities around ≈400 cm 2 V −1 s −1 , with Te having the significant advantage of utilizing a low‐temperature, scalable growth technique, compatible with heterogeneous 3D integration and flexible devices.…”
mentioning
confidence: 92%
“…We have shown the ability of low-temperature-grown (<500 • C) poly InAs thin films to achieve remarkable electron mobilities when measured at room temperature (~100 cm 2 /V•s), despite appearing non-uniform. The room-temperature Hall electron mobility of 155 cm 2 /V•s achieved for a heterostructure consisting of 25 nm poly GaAs + 25 nm poly InAs grown on glass (Table 1) exceeds the reported Hall mobility values of a number of other low-temperaturegrown thin-film materials, such as polycrystalline silicon [23], Hf-doped In 2 O 3 [24], ITO [25], and ZnO [26,27]. Temperature-dependent Hall effect measurements showed that surface roughness is the dominant factor limiting the electron mobility in the films, which points towards developing a planarization method for poly InAs films.…”
Section: Discussionmentioning
confidence: 59%
“…These observations could be attributed to local atomic rearrangement, the amorphous structure randomness relaxation, and trap states density reduction. The local atomic rearrangement and structure relaxation caused by ELA heating, provided that no crystallisation occurs, would enhance the overlap among ns orbitals of the contained metals leading to better carrier mobility [2,11,12]. The highest observed Hall effect mobility in this work was 13.9 cm 2 /Vs obtained by ELA with single pulse at 100 mJ/cm 2 , which is very promising to apply laser treated IGZO to IGZO TFTs.…”
Section: Discussionmentioning
confidence: 68%
“…For IGZO-TFT devices, thermal and laser annealing IGZO channel layer patterns result enhanced electrical performance of IGZO TFTs. This is originated from induced changes in IGZO layers upon annealing including reduction of scattering or trapping defects density on the bulk IGZO or at its interface, enhanced atomic bonding, and amorphous structure relaxation leading to enhanced electrical prosperities of IGZO [2,11,12]. laser irradiation is also expected to reduce the contact resistance between the IGZO channel layer and the source/drain electrodes due to reduction of IGZO channels resistivity and increasing the carrier concentration upon ELA.…”
Section: Discussionmentioning
confidence: 99%